2015
DOI: 10.5935/0004-2749.20150012
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent myopic foveoschisis: resolution after internal limiting membrane removal

Abstract: We report a case of a 66-year-old man with a history of high myopia and who was referred for acute decreased visual acuity of the right eye. Fundus examination and optical coherence tomography (OCT) showed a mild epiretinal membrane (ERM) and splitting of retinal layers. Pars plana vitrectomy was performed with intravitreous triamcinolone injection, posterior hyaloid and ERM peeling, and 12% perfluoropropane (C3F8) gas tamponade. After remaining asymptomatic for 17 months, the patient reported a new episode of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(17 reference statements)
0
3
0
1
Order By: Relevance
“…However, after undergoing PPV combined with ILM peeling, there was no recurrence at the 6-month follow-up, and the BCVA improved to 20/25. An OCT examination revealed significant improvement in the macular structure [ 25 ]. Moreover, Sayanagi et al described two cases of patients with refractory MF.…”
Section: Discussionmentioning
confidence: 99%
“…However, after undergoing PPV combined with ILM peeling, there was no recurrence at the 6-month follow-up, and the BCVA improved to 20/25. An OCT examination revealed significant improvement in the macular structure [ 25 ]. Moreover, Sayanagi et al described two cases of patients with refractory MF.…”
Section: Discussionmentioning
confidence: 99%
“…**level of significance, p < 0.01. ***level of significance, p = 0.001 [40,44]. Ikuno et al suggested that with foveal can obtain the most functional benefit from surgery compared to other [18].…”
Section: Discussionmentioning
confidence: 99%
“…ILM peeling has been suggested to increase the surgical success rate in all stages of myopic foveoschisis [17,24,28,30,31,35,[40][41][42], ensuring that all residual hyaloid and ERM are removed and increasing retinal adhesion to the posterior staphyloma. Despite ILM peeling in highly myopic eyes is technically challenging, it has been suggested that a wider peel area overlying the staphyloma may be useful, as we observed.…”
Section: Discussionmentioning
confidence: 99%
“…In this condition, vitrectomy is a relatively more suitable surgical strategy, which can remove the posterior vitreous cortex and abnormal vitreomacular traction. On the other hand, for significant axial elongated eyes, especially combined with posterior scleral staphyloma, vitrectomy alone is not enough to for foveoschisis relief and macular reattachment [11][12][13] . In our previous study, we compared the surgical outcome of PSR followed by vitrectomy and vitrectomy alone on MF of extremely pathologic myopic eyes.…”
Section: Introductionmentioning
confidence: 99%